2014
DOI: 10.5812/ircmj.18129
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Modeling of Colonic Lesions With Geographic Information Systems

Abstract: Background:Geographic information system (GIS) software has been used in health care systems to display and analyze spatial pattern of diseases and health services.Objectives:This study was performed to assess spatial patterns of colon’s pathologic lesions based on the pathologic reports and assess whether it is possible to use GIS software in health services.Patients and Methods:Archives of pathology of Namazi and Faghihi hospitals, two main referral centers of south-west of Iran, were obtained and reviewed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Migraine is a common condition consisting of primary headaches with a prevalence of 15% in Western societies [ 31 ]. Secondary headache is frequently reported by patients with various gastrointestinal disorders such as gastroesophageal reflux disease, inflammatory bowel syndrome, constipation, functional abdominal pain, or H. pylori infection, but the potential causal link remains unclear [ 32 , 33 ]. However, in recent years, research has focused on the implication of H. pylori activity in the pathogenesis of migraine, as this microorganism was identified as a cause for multiple extra digestive manifestations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migraine is a common condition consisting of primary headaches with a prevalence of 15% in Western societies [ 31 ]. Secondary headache is frequently reported by patients with various gastrointestinal disorders such as gastroesophageal reflux disease, inflammatory bowel syndrome, constipation, functional abdominal pain, or H. pylori infection, but the potential causal link remains unclear [ 32 , 33 ]. However, in recent years, research has focused on the implication of H. pylori activity in the pathogenesis of migraine, as this microorganism was identified as a cause for multiple extra digestive manifestations [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…2, 3 Appendix lumen obstruction is a triggering factor of appendicitis, one of which is caused by constipation due to poor eating habits. 4 MH Imanieh (2007) revealed that out of 31 appendicitis patients with constipation, 58% reported not eating fruits regularly, and only 9.7% consumed vegetables daily. 5 Imanieh concluded that the high level of constipation in patients with lower fiber intake is in line with the hypothesis that dietary fiber plays a role in reducing the incidence of appendicitis.…”
Section: Introductionmentioning
confidence: 99%
“…4 MH Imanieh (2007) revealed that out of 31 appendicitis patients with constipation, 58% reported not eating fruits regularly, and only 9.7% consumed vegetables daily. 5 Imanieh concluded that the high level of constipation in patients with lower fiber intake is in line with the hypothesis that dietary fiber plays a role in reducing the incidence of appendicitis. 5 Based on research conducted by Fitriana S (2013), it was found that the type of food consumed, especially highfiber food, was related to the incidence of appendicitis in Regional General Hospital Kab.…”
Section: Introductionmentioning
confidence: 99%
“…Geographic information system (GIS) in the format of computer software tools constitutes a powerful approach to store, analyse and manage epidemiological data. Although GIS is mainly applied for the investigation of the localisation and distribution of cases of various diseases in the environment, it can also be used for the positioning of pathology of organs in the body, as described by Daraban et al (2014), Pascotto et al (2014), and Imanieh et al (2015). The aim of present investigation was to determine the topographic distribution of gastritis lesions in pigs through the application of open source GIS software.…”
Section: Introductionmentioning
confidence: 99%